NETWORK ORGANIZATIONS IN POSTMODERNITY (Dissertare, 2022)
The objective of this research work is to describe reticular organizations, as part of the current postmodern culture and its particular link with the context of the covid-19 pandemic. The focus of the work is qualitative, with documentary design, supported by the bibliographic review as a technique for collecting information, and the hermeneutic method for the purposes of analysis. The development of the work shows that this type of organization is mainly characterized by being flexible, which allows them to adapt to the current turbulent environment, disorder, indeterminacy and chaos, among other elements. In addition, it has structural and cultural processes and facets that foster the creation, acquisition and transfer of knowledge, change, continuous learning, development and creativity. It is concluded that the reticular organization is virtual, learning, complex, strengthened in multi-agent systems; it relies in a special way on new network interconnectivity technologies, its network topology is representative of its organizational structure, it requires a strategic deployment based on uncertainty, it uses creative chaos in favor of innovation; and additionally, in the context of the covid-19 pandemic, it turns out to be the best option for organizational work because it allows the remote integration of activities through telematic networks.
Keywords: reticular organization; network topology; learning organization; strategic deployment; creative chaos